A RADical Idea: A Call to Eliminate "Attachment Disorder" and "Attachment Therapy" From the Clinical Lexicon. Issue 1 (2nd January 2016) - Allen, Brian
ABSTRACT: "Attachment disorder" and "attachment therapy" are common terms used in applied clinical practice. However, these terms are not typically employed in research settings or published scientific papers. In this article, the author reviews the theoretical tenets and empirical research of attachment theory and discusses how these two terms fail to coincide with the scientific knowledge. The historical development of these phrases is considered, as well as the potential impact they have on clinical practice. The ultimate conclusion is that the "attachment disorder" and "attachment therapy" constructs are hindrances to evidence-based clinical practice and should be eliminated from the clinical lexicon.